A look at the things that affect modern farmers' income - Surbakti, Wira Surya Cendikia; Sabirin, Sabirin (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2023)
This study aims to analyze the effect, capital, land area, labor on the income of modern farmers (Hydroponics) in Palangkaraya City. The research method used in this study is a quantitative approach method and uses primary data sourced from hydroponic farmers in the research location obtained by interviewing respondents, Palangkaraya City. Data were analyzed using multiple linear regression analysis methods. The results of this study indicate that capital and land area have a positive and significant effect on the income of modern farmers (Hydroponics) in Palangkaraya City, labor has a positive and insignificant effect on the income of modern farmers (Hydroponics) in Palangkaraya City. From the results of this analysis, it can be suggested that the Palangkaraya City government helps hydroponic farmers who want to start modern hydroponic agriculture in Palangkaraya City by lending capital to farmers who want to start hydroponic farming but lack capital, for small land areas, farmers can plant hydroponic crops in stages so that the harvest yields more, workers should use the family so that income does not decrease